Echoes of 1935, Signals of 2025: A 90-Year Journey - de Percy, Michael (Journal of Telecommunications and the Digital Economy, 2025)
This editorial bridges the past and future of telecommunications and the digital economy. It highlights the third collaboration with the International Conference on Digital Economy, following its ninth conference in Morocco in 2024. The conference inspired the Special Issue section, ‘Driving the Digital Economy with Cutting-Edge Technologies, Innovation, and Data Analytics,’ alongside the Telecommunications articles in this March 2025 issue. These contributions signal the Journal’s forward-looking vision. Meanwhile, the Biography and History sections reflect on the Journal’s legacy, marking the 90th anniversary of continuous publication. The editorial concludes with gratitude to the outgoing Managing Editor for his pivotal support during the new Editor-in-Chief’s inaugural issue.